A Lithium‐Organic Primary Battery. Issue 3 (23rd December 2019) - Sun, Pengfei; Bai, Panxing; Chen, Zifeng; Su, Hai; Yang, Jixing; Xu, Kang; Xu, Yunhua
Abstract: Lithium primary batteries are still widely used in military, aerospace, medical, and civilian applications despite the omnipresence of rechargeable Li‐ion batteries. However, these current primary chemistries are exclusively based on inorganic materials with high cost, low energy density or severe safety concerns. Here, a novel lithium‐organic primary battery chemistry that operates through a synergetic reduction of 9, 10‐anthraquinone (AQ) and fluoroethylene carbonate (FEC) is reported. In FEC‐presence, the equilibrium between the carbonyl and enol structures is disabled, and replaced by an irreversible process that corresponds to a large capacity along with methylene and inorganic salts (such as LiF, Li2 CO3 ) generated as products. This irreversible chemistry of AQ yields a high energy density of 1300 Wh/(kg of AQ) at a stable discharge voltage platform of 2.4 V as well as high rate capability (up to 313 mAh g −1 at a current density of 1000 mA g −1 ), wide temperature range of operation (−40 to 40 °C) and low self‐discharge rate. Combined with the advantages of low toxicity, facile and diverse synthesis methods, and easy accessibility of AQ, Li‐organic primary battery chemistry promises a new battery candidate for applications that requires low cost, high environmental friendliness, and high energy density. Abstract : A novel lithium‐organic primary battery chemistry is demonstrated by activating the irreversible reaction of anthraquinone cathode by fluoroethylene carbonate, which delivers a high specific capacity of 575 mAh g −1 and density of 1300 Wh kg −1 . The mechanism is systematically investigated and revealed to be that the carbonyl groups are electrochemically reduced to methylene accompanied by generation of a large amount of salts.